2013
DOI: 10.1111/jcal.12039
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the learning potential and students' perception of rich lecture captures

Abstract: There is a large variety of lecture capture forms being used today when considering their content and ways in which that content is being reproduced. The objective of this study was therefore to investigate the students' perception and the learning potential of lecture captures enriched using additional learning contents compared to lecture captures containing only the video and audio recording of the lecturer and his slideshow. In an experiment in which students were learning using each of those two types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…At the second measuring point, there was a relative reduction in the perception of a contribution by the ClassBoost system to learning from the student teachers' viewpoint. This aspect is in line with the findings of previous research, which found that use of LCT was not expressed in alterations in the learners' achievements (Bollmeier et al, ; Drouin, ; Hadgu, Huynh, & Gopalan, ; Pale et al, ). We estimate that the reduction in the perception of the contribution of the ClassBoost system to learning is also connected to the fact that not all the qualities of the ClassBoost system were exploited, and the students did not know about or were not exposed to all the means and possibilities of this system.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…At the second measuring point, there was a relative reduction in the perception of a contribution by the ClassBoost system to learning from the student teachers' viewpoint. This aspect is in line with the findings of previous research, which found that use of LCT was not expressed in alterations in the learners' achievements (Bollmeier et al, ; Drouin, ; Hadgu, Huynh, & Gopalan, ; Pale et al, ). We estimate that the reduction in the perception of the contribution of the ClassBoost system to learning is also connected to the fact that not all the qualities of the ClassBoost system were exploited, and the students did not know about or were not exposed to all the means and possibilities of this system.…”
Section: Discussionsupporting
confidence: 92%
“…The student teachers revealed willingness to integrate collaborative technology in their learning (Roblyer et al, ), but as emerged from the qualitative part of the present research and from previous studies, their collaborative learning practices focused on communication and sharing knowledge at the most basic level (Romero & Lambropoulos, ) and did not develop to the stage of shared construction of ideas and problem‐solving (Inayat et al, ). The motivation for collaborations was extrinsic and did not cause a change in practices (Pale et al, ). The ClassBoost system is based on 21st century skills, including collaborative learning practices and emphasis is given to the affinity between pedagogy and a dynamically changing learning environment (Bower et al, ; Ertmer & Ottenbreit‐Leftwich, ; Sadaf et al, ; Tondeur et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Classic lecture capture refers to a system of recording video and audio. Rich lecture capture includes computer screen capture and document camera capture (Pale, Petrović, & Jeren, 2013). In some rich lecture capture, a picture-in-picture format is used with the majority of the screen devoted to the computer screen or document camera capture but with a small window of the speaker to help the viewer get a sense of the presentation subtleties.…”
Section: Literature Reviewmentioning
confidence: 99%
“… 1 Students generally welcome this added resource because it provides them with choice over the location, pace, and frequency of viewing lecture content. 2 6 In contrast, faculty instructors tend to be more skeptical of this technology, especially regarding its presumed impact on lecture attendance. 7 – 9 Romanelli et al 10 argue that declining attendance at lectures has both professional and educational consequences.…”
Section: Introductionmentioning
confidence: 99%